2013
DOI: 10.1152/ajplung.00116.2013
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation in nasal epithelial cells from smokers: identification of ULBP3-related effects

Abstract: -We previously demonstrated that, in nasal epithelial cells (NECs) from smokers, methylation of an antiviral gene was associated with impaired antiviral defense responses. To expand these findings and better understand biological mechanisms underlying cigarette smoke (CS)-induced modifications of host defense responses, we aimed to compare DNA methylation of genes that may play a role in antiviral response. We used a two-tiered analytical approach, where we first implemented a genome-wide strategy. NECs from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 41 publications
(61 reference statements)
1
19
0
Order By: Relevance
“…As in the present work, some studies have reported epigenetic alterations in healthy samples of smokers and it has been shown in blood cells, [13][14][15][16]68 sputum, small airway epithelium 69 and nasal epithelial cells 70 including studies with MLH1. 20,71 These data are extremely important because, as already suggested, it could be possible to predict cases of cancer, i.e.…”
Section: Tp53supporting
confidence: 71%
“…As in the present work, some studies have reported epigenetic alterations in healthy samples of smokers and it has been shown in blood cells, [13][14][15][16]68 sputum, small airway epithelium 69 and nasal epithelial cells 70 including studies with MLH1. 20,71 These data are extremely important because, as already suggested, it could be possible to predict cases of cancer, i.e.…”
Section: Tp53supporting
confidence: 71%
“…This will make studying the chronic effects of E-Cigs difficult since the airways/lung retain a significant memory of smoking history/exposure even after smoking cessation. For example, Rager et al found significant evidence of DNA methylation in the nasal epithelia of ex-smokers (121). Thus, for any observed effects on E-Cig smokers, the previous and/or current tobacco smoking history must be taken into account.…”
Section: Effects Of E-cig Aerosols and E-liquids On Cultured Cells Frmentioning
confidence: 99%
“…For example, nasal epithelial cells from smokers have unique DNA methylation patterns as compared with nonsmokers, and this results in altered expression of antiviral genes in vitro (18). Taken together, our studies suggest one putative immune pathway by which airway epithelium of very young children may exhibit enhanced susceptibility to pathogens.…”
mentioning
confidence: 69%
“…Epigenetic regulation of gene expression in airway epithelium is evident in inflammatory conditions like asthma, smoking, and infection; TSA has been instrumental in uncovering the role of histone acetylation in some of these studies (18,(31)(32)(33). Although TSA is an inhibitor of most of the class I and II HDAC proteins, its activity is restricted outside of the HDAC family of proteins (34).…”
Section: Discussionmentioning
confidence: 99%